1992
DOI: 10.1007/bf00296778
|View full text |Cite
|
Sign up to set email alerts
|

In vitro formation of mineralized nodules by periodontal ligament cells from the rat

Abstract: The purposes of this study were to determine whether periodontal ligament (PDL) cells are capable of producing mineralized nodules in vitro and to analyze ultrastructural features of the nodules. Rat PDL cells were obtained from coagulum in the socket at 2 days after tooth extraction and cultured at confluence in standard medium containing Dulbecco's Modified Eagle's Medium supplemented with 10% FBS and antibiotics. To test mineralized nodule formation, cells were further cultured for an additional 3 weeks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
2
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 31 publications
5
76
2
2
Order By: Relevance
“…There was also an absence of nodule formation and matrix mineralization: only aggregated cells with light alizarin red S staining was observed for hPDL cells treated with ascorbic acid and β-GP. These results well agreed with previous studies which suggested that nodule formation of hPDL cells mostly occurred in certain condition such as in the presence of dexamethasone, estradiol, or EMD with TGF-β1 13,29,30) . To confirm the potency of noni leaf extract in inducing osteogenic differentiation and matrix mineralization, a mouse preosteoblast cell line (MC3T3-1) was treated with the optimal concentration of 2.5% of noni leaf extract.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There was also an absence of nodule formation and matrix mineralization: only aggregated cells with light alizarin red S staining was observed for hPDL cells treated with ascorbic acid and β-GP. These results well agreed with previous studies which suggested that nodule formation of hPDL cells mostly occurred in certain condition such as in the presence of dexamethasone, estradiol, or EMD with TGF-β1 13,29,30) . To confirm the potency of noni leaf extract in inducing osteogenic differentiation and matrix mineralization, a mouse preosteoblast cell line (MC3T3-1) was treated with the optimal concentration of 2.5% of noni leaf extract.…”
Section: Discussionsupporting
confidence: 93%
“…The ability to grow and manipulate stem cells within the periodontal ligament is of considerable clinical significance, especially for developing novel mechanisms to achieve bone and periodontal tissue regeneration 28) . Previous findings have indicated that hPDL cells possess several osteoblast-like properties, including the ability to form mineralized nodules in vitro 13,29) when cultured in the presence of growth factors such as enamel matrix derivative (EMD) and transforming growth factor-beta1 (TGF-β1) 30) . However, not only is EMD costly, clinical and cell culture studies have yielded controversial and conflicting results 32) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been revealed that PDL tissue possesses multipotential mesenchymal stem cells that can differentiate into mineralized tissue-forming cells such as osteoblasts and cementoblasts (2,3). In fact, in vitro maintained PDL cells have various osteoblast-like properties, including the capacity to form mineralized nodules, expression of bone-associated markers, and response to bone-inductive factors such as bone morphogenetic protein 2 (BMP-2) (4,5). Interestingly, however, PDL tissue is never ossified in vivo under normal circumstances.…”
Section: Periodontal Ligament (Pdl)mentioning
confidence: 99%
“…Based on these findings, osteogenic and non-osteogenic cell lines appeared to have been isolated from the original heterogeneous HPL population. Since HPL cells form bone-like mineralized nodules in the presence of ascorbic acid, β-glycerophosphate and dexamethasone in monolayer cultures (29,30), we evaluated the mineralization activity of the original HPL cells and the 2 clones expressing the highest and lowest of ALP activity (A4 and C10, respectively). We also looked for mRNA expression of osteogenic markers ALP, Cbfa1, BMP-2, BMP-4, and OCN, each of which has a unique distribution within the periodontium, and plays important role in cementogenesis and osteogenesis (31,32).…”
Section: Discussionmentioning
confidence: 99%